Collaborative capital creating intangible value - Beyerlein, Michael Martin; Beyerlein, Susan T.; Kennedy, Frances A. (Emerald, 2005)
Intangible forms of capital are being recognized in both research and practice as essential resources for fueling company growth. Forms of intangible capital include: intellectual, organizational, human, relationship, social, political, innovation, and collaborative. This volume consists of papers that focus on collaborative capital - broadly defined as the organizational assets that enable people to work together well. It is manifested in such outcomes as increased innovation and creativity, commitment and involvement, flexibility and adaptability, leveraging of knowledge, and enhanced learning. 'Collaborative capital' represents a core competency or strategic resource essential for building competitive advantage by enabling the creation of networks of conversations and relationships. However, it is seldom developed in a deliberate and systematic way, but rather as an incidental outcome of formal and informal organizational change. It may be deliberately increased by change in organizational systems, practices, design, learning, and culture. The term collaborative capital has seldom been used in research literature dealing with how people work together. Consequently, the meaning, measurement, and impact of collaborative capital in practice have not been explored to any significant extent. The papers in this volume launch that process with teaming contexts ranging from alliances and partnerships, to cross-national teams and cross-disciplinary teams.
Keywords: Intellectual capital.; Knowledge management.; Personnel management.; elektronické knihy; electronic books